Growth pattern of stock cultures of five selected species of marine microalgae maintained under indoor controlled environment and under outdoor conditions - Ajithkumar, P. B.; Joseph, Shoji; Vidya, K. (Indian Journal of Fisheries, 2019)
Growth pattern of five species of microalgae viz., Chaetoceros calcitrans, Dunaliella sp., Isochrysis galbana, Tetraselmis tetrahele and Nannochloropsis salina were studied under indoor controlled conditions (at 230C) and under outdoor (at 28-30Â°C) conditions. The variations in ammonia and pH levels in the culture flasks over a period of 90 days were also studied. Results revealed that the pattern of growth of all five species of algae were significantly different (p<0.05) in the two different conditions. The results clearly showed that the growth of all the five species of algae were faster in outdoor conditions and outdoor cultures were able to maintain only for a maximum period of three months. Ammonia and pH levels recorded were higher in outdoor cultures which indicated higher physiological activities and growth. Ammonia and pH levels were found to increase gradually in all the cultures, upto 30 days under both conditions and subsequently found almost constant throughout the study. Even though ammonia levels were found to rise with increase in pH and temperature, it did not increase to a level that is detrimental to the microalgal cultures.